2008
DOI: 10.2337/db07-0900
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Single Nucleotide Polymorphisms Identifies Major Type 1A Diabetes Locus Telomeric of the Major Histocompatibility Complex

Abstract: (DR3/4-DQ8) siblings who share both major histocompatibility complex (MHC) haplotypes identical-by-descent with their proband siblings have a higher risk for type 1A diabetes than DR3/4-DQ8 siblings who do not share both MHC haplotypes identical-bydescent. Our goal was to search for non-DR/DQ MHC genetic determinants that cause the additional risk in the DR3/4-DQ8 siblings who share both MHC haplotypes. RESEARCH DESIGN AND METHODS-We completed an extensive single nucleotide polymorphism (SNP) analysis of the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(57 citation statements)
references
References 34 publications
4
52
1
Order By: Relevance
“…Both single SNPs and five-SNP haplotypes showed association in this region, and we also replicated the association observed here. Recently Aly et al 24 reported an association with T1D upstream of PRSS16, but this SNP (rs996247) showed no association in our dataset. However, overall there is a strong evidence for an association around the PRSS16 gene.…”
Section: Discussioncontrasting
confidence: 86%
See 2 more Smart Citations
“…Both single SNPs and five-SNP haplotypes showed association in this region, and we also replicated the association observed here. Recently Aly et al 24 reported an association with T1D upstream of PRSS16, but this SNP (rs996247) showed no association in our dataset. However, overall there is a strong evidence for an association around the PRSS16 gene.…”
Section: Discussioncontrasting
confidence: 86%
“…Furthermore, in the earlier T1DGC screen we have also reported association with SNPs near HLA-G, that is, rs4122198, rs1619379 and rs2394186, 25 and others have reported association with SNPs in the UBD/MAS1L region (particularly with rs1233478). 24 When conditioning on each of these SNPs (together with DRB1-DQA1-DQB1 and HLA-B), the association with the SNPs in the extended class I region remained significant and vise versa, except for the PRSS16 SNP rs9393796 when adjusting for rs2394186 (data not shown). Both these SNPs seemed to reduce each other's effect, thereby indicating some sort of dependency between these associations.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…A DRB1-DQA1-DQB1-independent association between T1D and certain HLA-B alleles has been demonstrated in several reports, [3][4][5][6]10,18 but most convincingly by a British combined case-control/family study 3 and in a large family material provided by the T1DGC. 18 In both earlier studies and this study, the most consistent evidence was observed for the B*39 and B*18 alleles, with demonstrated independence of a high number of neighboring markers.…”
Section: Confirmation Of Mhc Class I Associationsmentioning
confidence: 83%
“…1,2 However, numerous studies have strongly implicated additional T1D risk loci within the MHC. [3][4][5][6][7][8][9][10][11][12] This complex contains an unusually high density of genes involved in immunological responses, 13 of which many are good candidates for involvement in autoimmune processes. The observation of multiple susceptibility loci in the MHC is shared with a number of other AIDs, including ankylosing spondylitis, celiac disease, Graves' disease, juvenile idiopathic arthritis, multiple sclerosis, rheumatoid arthritis, sarcoidosis, systemic lupus erythematosus and ulcerative colitis (cf.…”
Section: Introductionmentioning
confidence: 99%